Role of Kindlin-2-Expressing Extracellular Vesicles in the Invasiveness of Triple Negative Breast Cancer Tumor Cells - Neelum Aziz Yousafzai; Mark F. Santos; Yeaji Kim; Nofar Avihen Schahaf; Kim Zielke; Lucia Languino; Khalid Sossey-Alaoui; Aurelio Lorico (Cells, 2025)
Metastatic breast cancer (BC) is a major cause of cancer-related deaths among women. Its progression is influenced by extracellular vesicles (EVs) released by BC cells, which modulate distant tissue environments to promote metastasis. We previously identified the oncogenic protein Kindlin-2 (K2) as a key driver of BC metastasis, including its role in the nucleus in regulating cell senescence. Here, we investigated whether K2-containing EVs facilitate both autologous (cancer-to-cancer) and heterologous (cancer-to-stroma) communication to promote metastasis. We found that 10–15% of EVs from metastatic BC cells contained K2, while this subpopulation was nearly absent in the EVs from K2-knockout (KO) cells, indicating selective packaging. These EVs transferred K2 to recipient K2-KO cells, where they accumulated in the nucleus. Using a 3D tumorsphere assay, we showed that K2+ EVs enhanced cancer cell invasiveness. Moreover, K2+ EVs activated fibroblasts into a cancer-associated phenotype, increasing α-SMA and FAP expression. Conditioned media from these activated fibroblasts further boosted cancer cell invasion. These results show that EV-associated K2 is actively transferred to recipient cells and regulates metastasis through nuclear signaling, suggesting K2+ EVs are critical mediators of BC progression and potential targets for therapy.